Varieties of the Himalayan eclogites: A pictorial review of textural and petrological features. (28th June 2017) - Rehman, Hafiz U.; Jan, M. Qasim; Khan, Tahseenullah; Yamamoto, Hiroshi; Kaneko, Yoshiyuki
Abstract: A pictorial review and brief description of metabasites (mainly eclogites) exposed in the western part of Himalaya, north Pakistan are presented. The metabasites occur in the Kaghan and Neelum valleys in the form of thick sheets, dikes, lenses, and zoned bodies. On the basis of petrography and mineral paragenesis, they can be distinguished into greenschist, amphibolites, garnet‐amphibolites, eclogites, amphibolitized eclogites, and garnetites. In this review, first a brief history of the term eclogite and its origin for understanding the process of eclogite formation is presented. Then, a description on the occurrence of various metabasites/eclogites outcrops in the western Himalaya is given. Later, detailed petrological and textural features observed in hand specimen and under the microscope are discussed for individual rock types. Finally, an overview of the Himalayan metabasites tracing back from their magmatic basaltic source to their transformation into amphibolites and eclogites via multi‐stage metamorphism is provided. The field features, with the aid of petrological and geochemical evidence of these metabasites, help to constrain the tectono‐metamorphic evolution of the continent–continent collision type orogenic belts such as the India–Asia collision‐related Himalayan metamorphic belt. Abstract : A pictorial overview of the metabasites (mainly eclogites) in western Himalaya, Kaghan Valley are presented. Based on field occurrence, petrography, mineral paragenesis, and age data, we discuss starting from their magmatic source and end up with their metamorphic evolution due to the continent–continent collision and subduction‐related tectonics processes. Abstract : 　パキスタン北部,   ヒマラヤ西部地域の塩基性変成岩類(主にエクロジャイト)を画像によって概観する,   同地域のカーガーン・バレーおよびニーラム・バレーには,   緑色片岩,   角閃岩,   ざくろ石角閃岩,   エクロジャイト,   角閃岩化したエクロジャイト,   およびざくろ石岩が岩脈,   岩床,   あるいはレンズ状岩体として産出する.  本稿では,   まず「エクロジャイト」という用語の歴史的背景を述べ,   次にヒマラヤ西部の塩基性変成岩類の様々な産状を記述し,   個々の岩型について標本から顕微鏡スケールの岩石学的記載を行う.  最後にヒマラヤの塩基性変成岩類の起源,   およびエクロジャイトに至るまでの変成過程についての知見を取りまとめ,   インドとアジアの衝突テクトニクスの枠組みにおけるヒマラヤ変成帯の形成メカニズムを展望する.